Gastrointestinal problem among Indian adults: Evidence from longitudinal aging study in India 2017–18 - Dawoodi, Sameer; Dawoodi, Inshiya; Dixit, Priyanka (Frontiers in Public Health, 2022)
Introduction: Diseases and illnesses of the gastrointestinal system have grown in the last decade due to considerable lifestyle changes. Therefore, this study aims to explore the factors associated with the self-reported gastrointestinal problems among the Indian elderly and to explore the relationship between non-communicable diseases such as hypertension, heart diseases, diabetes, and neurological or psychiatric and gastrointestinal disorder. Methods: This study uses data from the Longitudinal Ageing Study in India (LASI), a population-based national survey, conducted during 2017-2018 with a representative sample of 72,250 individuals. Descriptive statistics were used to provide the frequency distribution of sociodemographic and economic profiles of adults. Bivariate analysis was used to understand the percentage distribution of adults suffering from gastrointestinal problems by their background characteristics. Binary logistic regression was used to determine the factors associated with gastrointestinal problems. In the binary logistic regression analysis, a systematic model building procedure was adopted. Results: Overall prevalence of self-reported gastrointestinal problems was 18% with significant variations among regions, and it substantially increased with the increasing age of men. Hypertension and neurological problem have significant individual effects on gastrointestinal problems. Prevalence was higher among those who suffered from neurological or psychiatric problems (27%) than those who suffered hypertension (22%) and heart disease (23%). Adults from age group 45-54 (1.11, p<0.01) and 55-64 (1.09, p<0.01) years were significantly more likely to have gastrointestinal problems compared to the <44 age group. Formerly and currently smokers and adults with habits of chewing tobacco were significantly more likely to report gastrointestinal problems than their counterparts. Moreover, the increasing economic status significantly and positively increased the likelihood of having self-reported gastrointestinal problems among adults. Conclusions: Ageing related gastrointestinal problems are physiological or pathological and more prevalent in the elderly population aged 64 years and above. Hence, policies and interventions have to be made age-specific. Gastrointestinal problems among the elderly are acquiring greater importance in clinical practices to plan effective treatment, administration of gastrointestinal drugs, early screening of gastrointestinal diseases. Given the policy focus through Health & Wellness centres for accessible NCD care, it is important that gastro-intestinal illnesses receive more focus and systemic support.